2015
DOI: 10.1016/j.comppsych.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The role of alexithymia in predicting incident depression in patients at first acute coronary syndrome

Abstract: Our results do not support the hypothesis that alexithymia at TAS-20 is a risk factor for incident depression after acute coronary syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 80 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…At baseline, 304 subjects completed all questionnaires. Data from the same sample, or part of it (i.e., completers at 1-year follow-up), were published in previous articles aimed at evaluating risk factors for the development of an incident depressive disorder (Marchesi et al, 2014a, 2014b, 2015; Ossola, De Panfilis, Tonna, Ardissino, & Marchesi, 2015; Ossola, Paglia, et al, 2015). The patients flowchart is detailed in Figure 1…”
Section: Resultsmentioning
confidence: 99%
“…At baseline, 304 subjects completed all questionnaires. Data from the same sample, or part of it (i.e., completers at 1-year follow-up), were published in previous articles aimed at evaluating risk factors for the development of an incident depressive disorder (Marchesi et al, 2014a, 2014b, 2015; Ossola, De Panfilis, Tonna, Ardissino, & Marchesi, 2015; Ossola, Paglia, et al, 2015). The patients flowchart is detailed in Figure 1…”
Section: Resultsmentioning
confidence: 99%
“…However, several other studies have found that average reductions in alexithymia scores were independent of baseline clinical severity (Rufer et al, 2010) or reduction in clinical severity (Ogrodniczuk, Joyce, & Piper, 2013), and that reduction in clinical severity accounted for a nonsignificant amount of variance in reduction in alexithymia scores (de Timary, Luts, Hers, & Luminet, 2008;Luminet, Bagby, & Taylor, 2001;Melin et al, 2010;Ogrodniczuk, Sochting, Piper, & Joyce, 2012). In addition, while some longitudinal studies have found higher alexithymia scores to be associated with the development of psychiatric symptomatology in nonpsychiatric samples (McCaslin et al, 2006;Tolmunen et al, 2011), not all studies have found this (Marchesi et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…The present study is part of a more extensive investigation on never-depressed patients at their first ACS (Marchesi et al, 2014a(Marchesi et al, , 2014bMarchesi et al, 2015;Ossola et al, 2015aOssola et al, , 2015bOssola et al, , 2018.…”
Section: Resultsmentioning
confidence: 99%